Work stress, pay satisfaction, psychological empowerment and organisational commitment among academic staff - Darus, Amer; Azizan, Farah Lina; Ahmad, Fais (Universiti Utara Malaysia, 2016)
This study investigated the mediating effect of psychological empowerment on the relationship between work stress, pay satisfaction, and organisational commitment among academic staff in public universities.A total number of 297 academics responded to this study and Statistical Package Software for Social Science (SPSS) Version 21.0 was used to analyse the collected data.The results indicated that work stress is associated with organisational commitment, whereas pay satisfaction, psychological empowerment, and organisational commitment have significant relationships with each other.Furthermore, multiple regression analysis revealed that psychological empowerment partially mediated on the relationship between pay satisfaction and organisational commitment.It is recommended that future research could further extend by including non-academic staff as well.